2014
DOI: 10.1161/atvbaha.114.303211
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variation in Vitamin K Epoxide Reductase Gene Is Associated With Survival and Progressive Coronary Calcification in Chronic Kidney Disease

Abstract: Objective-Sequence variations in the gene(s) encoding vitamin K epoxide reductase complex subunit 1 (VKORC1), the enzyme target of warfarin, have been associated with increased cardiovascular disease in the general population. Coronary artery calcification (CAC) is a prevalent form of cardiovascular disease in chronic kidney disease. We tested the hypothesis that the VKORC1 rs8050894 CC genotype would be associated with mortality and progression of CAC ≤4 years. Approach and Results-This study is an observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…This presents a critical barrier to establishing the importance of vitamin K to CKD patients for all the aforementioned reasons. Indirect evidence of the role of VKDPs in coronary calcification and survival in CKD was provided in a genetic analysis of 86 CKD patients with data on CAC and 4-y survival rates (77). The gene of interest was VKOR , which is a critical enzyme in the recycling of vitamin K (see Figure 4).…”
Section: Evidence Of Vitamin K’s Role In Vascular Calcification and Ckdmentioning
confidence: 99%
“…This presents a critical barrier to establishing the importance of vitamin K to CKD patients for all the aforementioned reasons. Indirect evidence of the role of VKDPs in coronary calcification and survival in CKD was provided in a genetic analysis of 86 CKD patients with data on CAC and 4-y survival rates (77). The gene of interest was VKOR , which is a critical enzyme in the recycling of vitamin K (see Figure 4).…”
Section: Evidence Of Vitamin K’s Role In Vascular Calcification and Ckdmentioning
confidence: 99%
“…Importantly, this is not solely a pathology of drug side effects, as a threonine to alanine (Thr83Ala) polymorphism in MGP confers increased risk of CAC progression 58 . Emerging data suggesting sequence variations in the gene(s) encoding vitamin K epoxide reductase complex subunit 1 (VKORC1), the enzymatic target of warfarin, may also lend insight into high risk subpopulations of CAC progression and poorer survival rates 59 . While reports are mixed on the utility of phylloquinone (Vitamin K1) supplementation as a countermeasure to these pharmacological/biological side effects (which has been shown to both decrease 60 or increase risk of coronary artery calcification) 61 , a deeper understanding of interactions between drugs, genetics, and cardiovascular calcification will likely lead to novel potential therapeutic targets to slow progression of vascular calcification or counter significant side effects related to anticoagulation therapy.…”
Section: Leveraging Biomarkers To Guide Interventionmentioning
confidence: 99%
“…Multiple-recognized environmental factors including dyslipidemia, hypertension, diabetes mellitus, obesity, alcohol use, lack of physical activity, poor diet, tobacco use, and air pollution are linked to a high risk of CCVD (Kim and Johnston, 2011;Turin et al, 2012;Belanger et al, 2014). In light of the high incidence and mortality of CCVD, we are interested in the underlying mechanisms with an aim of identifying causative factors; thus, we noted recent studies that suggested the vitamin K epoxide reductase complex subunit 1 (VKORC1) gene as a leading candidate in the genetic predisposition to CCVD risk (Kim and Johnston, 2011;Owens, 2011;Holden et al, 2014).…”
Section: Introductionmentioning
confidence: 99%